IMPLEMENTASI METODE WAFA DALAM MENINGKATKAN MUTU PEMBELAJARAN AL-QUR’AN DI SMP MUHAMMADIYAH BOARDING SCHOOL TANGGUL JEMBER - Zakariya, Din Muhammad; Suwandi, Suwandi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The background of this research is related to the development of the various of Al-Qur'an learning methods, but the number of methods has not been comparable to the increasing quality of Al-Qur'an learning in educational institutions. Of the many methods of learning the Qur'an, one of them is based on a quality assurance system and has a real contribution to improving the quality of learning the Qur'an in formal education. This type of research is field research using qualitative research methods, data collection techniques are carried out through interviews, observations, and documentation, data obtained from primary and secondary sources. The results of the study on the quality of learning the Qur'an at SMP Muhammadiyah Boarding School Tanggul Jember included three stages. First, quality in the planning stage, Second, quality in the implementation stage, Third, quality in the evaluation stage. The implementation of the Wafa method in improving the quality of Al-Qur'an learning at SMP Muhammadiyah Boarding School Tanggul Jember is based on the standardization of Al-Qur'an learning the Wafa method through the 7M quality management system. Mapping, improving, standardizing, accompanying, supervising, munaqosyah and confirming.